The Relationship Between Smoking Habits And Exposure To Passive Cigarette Smoke With Symptoms Of ARI In Public Health Students - Enzelina Rosiana Tampubolon; Dwi Noerjoedianto; Budi Aswin; M. Ridwan; Ashar Nuzulul Putra (International Journal of Health Engineering and Technology, 2026)
Acute Respiratory Tract Infection (ARI) remains a common health problem among young adults and can disrupt academic productivity. Smoking and exposure to secondhand smoke are thought to increase respiratory tract vulnerability through mucosal irritation and decreased respiratory defense function. This study aims to analyze the relationship between smoking and secondhand smoke exposure with ARI symptoms in students of the Public Health Science Study Program, class of 2024, Jambi University. The study used a quantitative cross-sectional design with 100 students selected using a simple random sampling method. Data were collected using a structured questionnaire covering respondent characteristics, smoking status, secondhand smoke exposure, and ARI symptoms in the past month. Univariate and bivariate analyses were performed using the Chi-square test, Odds Ratio (OR), and 95% confidence intervals. The results showed that 42.0% of respondents experienced ARI symptoms, 12.0% were active smokers, and 54.0% were frequently exposed to secondhand smoke. Smoking habits were significantly associated with ARI symptoms (p=0.031; OR=5.00; 95%CI=1.26-19.80). Exposure to secondhand smoke was also significantly associated with ARI symptoms (p=0.042; OR=2.94; 95%CI=1.28-6.79). Gender was not significantly associated with ARI symptoms (p=0.788). Strengthening smoke-free areas and promoting smoking cessation education should be prioritized on campus and in student housing environments.